Case 3711: Iberolacerta Arribas and Darevskia Arribas (Chordata, Squamata, Lacertidae): proposals to deem these names available either from Arribas (1997) or from Arribas (1999) - Arribas, Oscar J; Ananjeva, Natalia B; Carranza, Salvador; Doronin, Igor V; Orlov, Nikolai L; Orlova, Valentina F (Bulletin of Zoological Nomenclature, 2018)
The purpose of this application under Articles 78.1 and 81 of the Code is to request the Commission to use its plenary power to choose among two alternatives in order to preserve the genus name Darevskia and nomenclatural stability. In Alternative A, the Commission is asked to accept the microfiche publication (Arribas, 1997) as a published work in the sense of the Code and made available the names included therein, placing Iberolacerta Arribas, 1997 and Darevskia Arribas, 1997 on the Official List of Generic Names in Zoology, their type species on the Official List of Specific Names in Zoology, and the microfiche edition of Arribas (1997) on the Official List of Works Approved as Available for Zoological Nomenclature. This action will promote stability, as both names are widely accepted and, if the 1997 publication in microfiche is considered unavailable, then Darevskia Arribas, 1997 could potentially be threatened by Caucasilacerta Harris et al., 1998 (by authors who would not consider this name a nomen nudum), which would clearly disrupt stability. Not only would this alternative be the best way to preserve nomenclatural stability as stressed in the ICZN Preamble and repeated in several Articles of the Code, but it would also be the only way to ensure that these names (available at the time of their publication) remain available after the retroactive changes that have been introduced between the third and fourth editions of the Code. If Alternative A is chosen, both Iberolacerta and Darevskia become available from Arribas (1997). In Alternative B, the microfiche publication (Arribas, 1997) is considered invalid and placed on the Official Index of Rejected and Invalid Works in Zoological Nomenclature. Both Iberolacerta and Darevskia would be considered published in Arribas (1999). Also, the Commission is asked to place on the Official Index of Rejected Generic Names in Zoology the name Caucasilacerta Harris et al., 1998 (as a nomen nudum due to the lack of a valid diagnosis) and to place on the Official List of Generic Names in Zoology the names Iberolacerta Arribas, 1999 and Darevskia Arribas, 1999.
Keywords: Nomenclature; taxonomy; Squamata; LACERTIDAE; Iberolacerta; Darevskia; Europe; Caucasus; Anatolia; Near East; microfiche edition; Caucasilacerta